A model of susceptibility to global consumer culture - Hernani-Merino, Martín; Mazzon, José Afonso; Isabella, Giuliana (Review of Business Management, 2015)
Objective – Since finding simililarities between cultures is an important aspect to defining global goods, this article proposes a model to characterize and verify the impact of traits that are latent to global consumers’ susceptibility to global consumer culture (SGCC) in acquiring global brands. Design/methodology/approach – Extensive literature review and analysis of issues referring to global consumption characteristics. Theoretical framework – Reviewed literature, integrated within a seven dimension SCCG model: compliance with consumer trends; social responsibility, perception of quality, social prestige, brand credibility, perceived risk and information costs saved; that may influence buying intention. Findings – As a result, we propose an integrative theoretical model of the dimensions that make up susceptibility to global consumer culture that lead consumers to acquire globally present brands. The proposed model incolved seven constructs that influence SCCG. We also included buying intention, which is the result of susceptibility. Originality/value – The proposed model allows for better understanding of the reasons why consumers tend to buy and consume global brands. With this model, it is possible to study in depth the individual differences that refer to personal preferences for brands as global symbols and meanings. It also contributes to the work of international managers, helping them develop global branding and positioning strategies focused on the different global markets in which a global brand is marketed.